PELATIHAN JUAL BELI MELALUI E-COMMERCE PADA MASYARAKAT - Titik Purwati; Miftah Rakhmadian; Ahmad Lani; Ruri Aisia Zaski; Siska Dewi Nawang Sari; Malikhah Malikhah (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2023)
Digitalization is a term that cannot be separated from discussions of the 21st century industry and information world. Digitalization itself is carried out in the context of increasing the efficiency and effectiveness of each part of performance, so that time and all available resources can be used as optimally as possible for the maximum profit. In the digital era, technological developments continue to run rapidly. It can be said that the development of technology in the digital era is a step that can be used to advance in society. This community service aims to provide training to the community so that they can take advantage of technological developments properly by providing workshops on using digital buying and selling platforms in Indonesia. These training and workshop activities were carried out in Paras Hamlet, Karangnongko Village, Poncokusumo District, Malang Regency. There are three stages in this community service activity, namely observation, planning and action. From these activities, the results obtained by the public can understand how to use the digital buying and selling platform, both acting as buyers and acting as sellers.